THE INFLUENCE OF SQ3R TOWARDS STUDENTS’ READING COMPREHENSION - IMAS OOM UMIASIH; SLAMET WAHYUDI YULIANTO; LUSIANA SUCIATI DEWI (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2019)
The purpose of the research was to investigate whether or not the influence of SQ3R (Survey, Question, Read, Recite, Review) towards students’ reading comprehension. The research was conducted in SMPN 2 Maja. This research used quantitative method and used non-equivalent control group design categorized as quasi experimental design. Two classes were selected from eighth grade as experiment and control class. The results of the data analysis were as follows. Mean score of pretest in experiment class was 58.96 and standard deviation was 13.980. While, mean score in control class was 58.93 and standard deviation was 12.450. Further, mean score of posttest in experiment class was 61.42 and standard deviation was 11.275. While, mean score of posttest in control class was 60.81 and standard deviation was 10.937.The result of T-test shows that value sig. (2-tailed) was 0.993 in pretest. It was higher than 0.05. Then, there was not difference of means between experiment and control class in pretest. The value sig. (2-tailed) was 0.848 in posttest. It was higher than 0.05. Then, there is not difference of means between experiment and control class in posttest. Based on the result of model summary in simple linear regression, R square was 0.022 with significance 0.490. It means that the influence of independent variable (questionnaire) towards dependent variable (posttest) was 2.2%. While, 93.6% influenced by other variable and significance 0.490 was higher than 0.05, then model of regressing was not good enough as predictors. Based on the coefficient, constant of 74.454. If there was nothing questionnaire, then value of posttest is 81.141. Regression coefficients X of (-0.312), it means each addition 1 value of questionnaire then decline of posttest value of 0.312. It shows that there was not the significant influence of SQ3R technique towards students’ reading comprehension.